Optimizing Bandicam in the Making of Video Presentations For Interactive Static Fluid Materials - Arif Rahman Hakim; Nur Iva Wulansari; Setyo Admoko (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
Covid 19 pandemic has had a significant impact on all aspects of life, one of which is education. Physics lesson that's previously conducted face-to-face then turned into virtual lesson with the use of online media. It raises problems for both students and teachers, especially in interacting the subject matter between students and teachers and understanding the subject matter. In addition, the students’ response to the lessons has decreased. This research aims to determine the effect of the Bandicam application on student's physics learning outcomes and to find out the student's response to the Bandicam application during physics teaching and learning process. The research method used the stages of ADDIE model development (Analysis, Design, Development, Implementation, and Evaluation). This study begins with a pre-test and then a post test is carried out after learning. The classes are divided into a control class and a treatment class, and are conducted using WhatsApp and Google Classroom. However, there are still some shortcomings on the conduct of the classes. This research was conducted for 11th graders majoring Mathematics and Natural Sciences (Class XI MIPA 1 and 2) at State Senior High School (SMA Negeri) 1 of Krian. It supports the physics learning process, especially for static fluid material. Bandicam application as a medium for learning physics can improve students’ cognitive learning outcomes in understanding physics. In addition, the students responded well to the use of this media because it provides innovation in terms of learning styles. Media can increase student's interest in learning physics, especially for static fluid material.